Pretreatment of Empty Fruit Bunches (EFB) for improved Enzymatic Saccharification - Rashid, Shah S,; Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail; Hamzah, Mohd. Salleh (2011)
To achieve an accomplished optimized condition for enzymatic saccharification of palm oil mill empty fruit bunches (EFB) for higher yield of sugar hydrolysis, a comprehensive pretreatment of EFB was carried out using the laboratory produced cellulase enzyme through bioconversion of palm oil mill effluent (POME) by the fungal strain Trichoderma reesei RUT C-30. The study was conducted by using two different types of agents such as physical and chemical. Heating, boiling and steaming are among the physical agents and different concentrations of nitric acid, sulfuric acid and sodium hydroxide (NaOH) were the chemical agents used for pretreatment of EFB to enhance the enzymatic saccharification of EFB. Among the physical pretreatment agents drying of EFB was found to be the best method and the maximum reducing sugar 99.06 mg/gm of EFB after 3 days (72 hours) was hydrolyzed from EFB which is 1.3 fold higher than the control. NaOH was proved to be the best among all the agents used in the pretreatment of EFB and 3% NaOH was far more effective on the enzymatic saccharification of EFB and 2.35 fold increment was achieved on the yield of reducing sugar (175.03 mg/gm of EFB) after 96 hours of incubation.